Reliability and relative validity of a child nutrition questionnaire to simultaneously assess dietary patterns associated with positive energy balance and food behaviours, attitudes, knowledge and environments associated with healthy eating - Magarey Anthea M; Wilson Annabelle M; Mastersson Nadia (BMC, 2008)
Abstract Background Food behaviours, attitudes, environments and knowledge are relevant to professionals in childhood obesity prevention, as are dietary patterns which promote positive energy balance. There is a lack of valid and reliable tools to measure these parameters. The aim of this study was to determine the reliability and relative validity of a child nutrition questionnaire assessing all of these parameters, used in the evaluation of a community-based childhood obesity prevention project. Methods The development of the 14-item questionnaire was informed by the aims of the obesity prevention project. A sub-sample of children aged 10-12 years from primary schools involved in the intervention was recruited at the project's baseline data collection (Test 1). Questionnaires were readministered (Test 2) following which students completed a 7-day food diary designed to reflect the questionnaire. Twelve scores were derived to assess consumption of fruit, vegetables, water, noncore foods and sweetened beverages plus food knowledge, behaviours, attitudes and environments. Reliability was assessed using (a) the intra class correlation coefficient (ICC) and 95% confidence intervals to compare scores from Tests 1 and 2 (test-retest reliability) and (b) Cronbach's alpha (internal consistency). Validity was assessed with Spearman correlations, bias and limits of agreement between scores from Test 1 and the 7-day diaries. The Wilcoxon signed rank test checked for significant differences between mean scores. Results One hundred and forty one students consented to the study. Test 2 (n = 134) occurred between eight and 36 days after Test 1. For 10/12 scores ICCs ranged from 0.47-0.66 (p < 0.001) while for two scores ICCs were < 0.4 (p < 0.05). Spearman correlations ranged from 0.34-0.48 (p < 0.01) and Cronbach's alpha 0.50-0.80. Three scores were modified based on this analysis. The Wilcoxon signed rank test found no evidence of a difference between means (p > 0.05) for 10/12 (test-retest reliability) and 3/7 (validity) scores. Conclusion This child nutrition questionnaire is a valid and reliable tool to simultaneously assess dietary patterns associated with positive energy balance, and food behaviours, attitudes and environments in Australian school children aged 10-12 years. Thus it can be used to monitor secular changes in these parameters and measure the effectiveness of this and other obesity prevention projects with similar aims.